Electropumping of water in nanochannels using non-uniform electric fields. (5th March 2023) - Xu, Yinxiang; Xu, Junbo; Liu, Huizhou; Yang, Chao
Graphical abstract: Highlights: Non-uniform electric fields induce the net flow of water confined within nanochannels. The net force derived from electric field gradients acts as the driving mechanism. The electropumping method proposed is more effective than Poiseuille flow. Electric fields enhance the ordered arrangements of water molecules in nanochannels. The extended Navier-Stokes (ENS) equation for electropumping water is proposed. Abstract: Pumping fluids at the nanoscale is of fundamental importance to nanofluidic systems. We perform molecular dynamics simulations and provide the extended Navier-Stokes (ENS) equation to prove the electropumping possibility of using non-uniform electric fields to induce the continuous and unidirectional net flow of water confined in nanochannels. The net flow can be seen as a result of the combined effects of the unidirectional orientation of water molecules and the net force induced by the electric field intensity difference between O and H atoms in a water molecule. Higher net flow rates can be achieved by enhancing the electric field intensity gradients through the characteristics parameter adjustment of external electric fields. Importantly, the electropumping is more effective than the pressure-driven flow due to the ordered arrangements of water molecules in electric fields. The ENS equation proposed is more applicable at the flow field with high order degree of water molecules.